A comprehensive study on the impacts of isolation heat exchangers on the energy performance of surface water heat pump systems. (June 2023) - Chen, Xiao; Wang, Yuqian; Zhu, Zhiwei; Tang, Jingyue; Zhou, Maojun
Highlights: Development of energy performance models for indirect and direct surface water heat pump systems. A method for energy-saving judgment between indirect and direct systems is provided. Case analysis in systemic view using developed models and energy-saving judgment method. An optimized system configuration for the case in this study is proposed. Abstract: Surface water heat pumps are included as a subset of ground-source heat pumps for the utilization of shallow geothermal energy. For the surface water heat pump applications in which the location of the heat pump plant is remarkably higher than water surface, the pump energy consumption of an indirect system with isolation heat exchangers (IHE) will be lower than that of a direct system without IHE. However, the entering fluid temperature of heat pumps in an indirect system is higher/lower than that in a direct system in cooling/heating modes due to the existence of IHE, which will bring a certain decrease in heat pump performance. This paper presents a comprehensive study on the impacts of IHE on system energy performance. The energy performance models for indirect and direct systems are developed, and a method for energy-saving judgment between indirect and direct systems is proposed. The case study results show that a direct system is more energy efficient for cooling than an indirect system because the elevation difference between water surface and plant is less than the critical value. Under low surface water temperature condition in winter, an indirect system using antifreeze fluid can eliminate the defect that the heating capacity of heat pumps in a direct system decreases much and auxiliary heat is needed. An optimized system configuration that combines the advantages of direct and indirect systems is proposed. The proposed system can operate without auxiliary heat in winter even though the surface water temperature drops to a low level, and can acquire cooling performance close to that of the cooling systems including chillers and cooling towers.